Photothermal-enhanced silver nanocluster bioactive glass hydrogels for synergistic antimicrobial and promote wound healing - Fuqiang Song; Anqi Ye; Linyuan Jiang; Yang Lu; Yanzhen Feng; Rong Huang; Siting Du; Xiaoyu Dong; Ting Huang; Ping Li; Liangliang Yang; Jinjing Zhang; et al. (Materials Today Bio)
Antibacterial hydrogels are promising for combating infections and promoting wound healing. Nevertheless, excessive antibiotics induce resistance, and high metal ion levels cause cytotoxicity, complicating healing. Here, we introduce a hydrogel incorporating polydopamine-coated bioactive glass (BGs@PDA) on reduced graphene oxide (rGO) with photothermal therapy (PTT) and silver nanoclusters (AgNCs) for synergistic antibacterial treatment. This design enables rapid bacterial eradication and controlled release. Near-infrared-assisted heating provides noninvasive, targeted hyperthermia, killing bacteria quickly. Post-PTT addition of low-dose AgNCs reduces toxicity while enhancing antimicrobial efficacy and biocompatibility. BGs@PDA-loaded rGO prevents sedimentation, improves photothermal conversion and conductivity, and stabilizes the hydrogel structure. Constructed from chitosan and hydroxyethyl cellulose, the hydrogel is cross-linked by PDA and rGO, enhancing mechanical strength, adhesion, self-healing, free radical scavenging, and continuous wound exudate absorption. PDA encapsulation facilitates BGs degradation, improving the wound microenvironment. In vivo studies confirm accelerated healing and potent synergistic antibacterial effects, indicating its potential as a low-dose, antibiotic-free alternative for clinical wound infection management.